 Kathleen Rausch

2021-12-27

To silve: $x\left(x-3\right)={x}^{2}+5x+7$ hysgubwyri3

Step 1
Distributive property is $a\left(b+c\right)=ab+ac$
Approach:
First, we have to take all the variables to our left side.
Then we have to take all the constants to our right side.
Remove any grouping symbols and solve the equation.
Step 2
To solve $x\left(x-3\right)={x}^{2}+5x+7$
By distributive property,
$x\left(x-3\right)=x×x-3×x$
$x\left(x-3\right)={x}^{2}-3x$
${x}^{2}-3x={x}^{2}+5x+7$
Add $-{x}^{2}-5x$ on both sides,
${x}^{2}-3x-{x}^{2}-5x={x}^{2}+5x+7-{x}^{2}-5x$
$-8x=7$
Divide by -8 on both sides,
$\frac{-8x}{-8}=\frac{7}{8}$
$x=-\frac{7}{8}$ psor32

Step 1
Given: $x\left(x-3\right)={x}^{2}+5x+7$
${x}^{2}-3x={x}^{2}+5x+7$
Step 2
Subtract ${x}^{2}$ from both sides
${x}^{2}-3x-{x}^{2}={x}^{2}+5x+7-{x}^{2}$
$-3x=5x+7$
Step 3
Subtract 5x from both sides
$-3x-5x=5x+7-5x$
$-8x=7$
Step 4
Divide both sides by -8
$\frac{-8x}{-8}=\frac{7}{-8}$
$x=\frac{-7}{8}$
The answer: $x=\frac{-7}{8}$ karton

Step 1
$x\left(x-3\right)={x}^{2}+5x+7$
Expand x(x-3) :
${x}^{2}-3x$
${x}^{2}-3x={x}^{2}+5x+7$
Subtract ${x}^{2}+5x$ from both sides
${x}^{2}-3x-\left({x}^{2}+5x\right)={x}^{2}+5x+7-\left({x}^{2}+5x\right)$
Simplify-8x=7
Divide both sides by -8
$\frac{-8x}{-8}=\frac{7}{-8}$
Answer: $x=-\frac{7}{8}$ (Decimal: x=-0.875)

Do you have a similar question?